PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KETERAMPILAN BERBICARA BAHASA INGGRIS - Doni Anggoro Ari Santoso; Zumrotul Muniroh; Nurul Akmaliah (Universitas Muria Kudus, 2019)
The purpose of this research is to find out the effect of the using of flash cards towards student’s speaking ability in STBA Pertiwi, Cileungsi. The researchers hope that this research can give advantages to all of lecturers and students in doing the learning process, especially in English speaking ability. The method used in this research is experiment method using two groups of classes. One class as experiment class, where the researchers are giving the materials using flash cards. While the other class is control class, where the materials are given with lecturing method. Based on the result of the data analysis, it can be concluded that the average score for English speaking ability in control class is 64,7. The median is 61.5. The modus is 57,5. The variance is 258, 6256. And the standard deviation is 16,082. In the other hand, the average score for English speaking ability in experiment class is 70,5. The median is 71,21. The modus is 85,056. The variance is 229, 128. And the standard deviation is 15,14. It is also obtained that the equation of Total Variance is 15,62. And the TObserved is 1,69 and the T table is 1,667. So that Tobserved bigger than Ttable; 1,69 bigger than 1,667 that is significant. It can be concluded that there is positive and significant effect of using of flash cards towards student’s speaking ability in STBA Pertiwi, Cileungsi.